2015
DOI: 10.1111/insr.12114
|View full text |Cite
|
Sign up to set email alerts
|

Posterior Inference in Bayesian Quantile Regression with Asymmetric Laplace Likelihood

Abstract: The paper discusses the asymptotic validity of posterior inference of pseudo-Bayesian quantile regression methods with complete or censored data when an asymmetric Laplace likelihood is used. The asymmetric Laplace likelihood has a special place in the Bayesian quantile regression framework because the usual quantile regression estimator can be derived as the maximum likelihood estimator under such a model, and this working likelihood enables highly efficient Markov chain Monte Carlo algorithms for posterior s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
101
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(103 citation statements)
references
References 68 publications
1
101
0
1
Order By: Relevance
“…whereΨ is the scaled variance-covariance matrix of w τ = u τ , v τ , and h 0 andḦ are the terms of order, respectively, 0 and 2 of the above-mentioned Taylor expansion around the modeŵ τ (see Appendix A for more details). When using the asymmetric Laplace as pseudo-likelihood, inference should be confined to point estimation (see for example Yang, Wang and He, 2016). Standard errors of non-random parameters estimates can be calculated using block bootstrap (Efron and Tibshirani, 1998), although this increases the computational cost.…”
Section: Similarly We Defineqmentioning
confidence: 99%
“…whereΨ is the scaled variance-covariance matrix of w τ = u τ , v τ , and h 0 andḦ are the terms of order, respectively, 0 and 2 of the above-mentioned Taylor expansion around the modeŵ τ (see Appendix A for more details). When using the asymmetric Laplace as pseudo-likelihood, inference should be confined to point estimation (see for example Yang, Wang and He, 2016). Standard errors of non-random parameters estimates can be calculated using block bootstrap (Efron and Tibshirani, 1998), although this increases the computational cost.…”
Section: Similarly We Defineqmentioning
confidence: 99%
“…Recently, both Yang, Wang, and He (2015) and Sriram (2015) proposed a correction to the MCMC iterations to construct asymptotically valid intervals. Their method builds on the work of Chernozhukov and Hong (2003) and Yang and He (2012).…”
Section: Controversies With the Ald Approachmentioning
confidence: 99%
“…In these papers, it is shown that the MCMC iterations provide a valid piece of the usual sandwich formula (see e.g., Koenker 2005) that can be used to construct a valid estimate of the limiting covariance matrix of the Gaussian approximation. The correction can be accomplished as follows (Yang et al 2015):…”
Section: Controversies With the Ald Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, to see the goodness of estimating the parameters based on the bias and variance values simultaneously, represented in the value of Mean Square Error (MSE) [8,9,10], formulated as follows :…”
Section: Mean Square Error (Mse)mentioning
confidence: 99%